Xplorasi3d 2.0: alternative self instruction material (SIM) in virtual reality for science - Hilmi, Syahir Bahiran; Yusof, Anuar; Sufahani, Suliadi Firdaus (Universiti Teknologi MARA, Kedah, 2023)
XPLORASI3D 2.0 is a Digital Game-Based Learning (DGBL) based on 3D Virtual Reality to help lower secondary students learn science subjects. It is challenging for teachers to teach digital native students to engage with the learning process that needs creative ways to attract students. These issues require the development of a new method of teaching and learning to improve students' interests and motivations, especially in the involvement of the 3D Virtual Reality software. XPLORASI3D 2.0 is a PC game that uses a computer, keyboard, mouse, or game pad as a controller.